Financial statement and budget report 1976-77 - Great Britain. H.M.S.O.; Great Britain. H.M.S.O. (London : H.M.S.O., 1998)
Copy of Financial Statement and Budget Report 1976-77 as laid before the House by the Chancellor of the Exchequer when opening the budget. The report covers: The economic background to the budget; Public sector transactions and Central government transactions.
"Copy of financial statement and budget report ... as laid before the House of Commons by the Chancellor of the Exchequer when opening the budget."
Some issues have also a distinctive title.
rpm 20/02/2019
Ref
Keywords: Financial statements; Economic policy; Finance, Public; Great Britain